Stimuli-Responsive Interfaces Fabrication and Application - Kawai, Takeshi; Hashizume, Mineo (Springer Nature Singapore : Imprint: Springer, 2017)
This book introduces recent progress in stimuli-responsive interfaces constructed on colloidal materials such as micelles and vesicles and on solid material surfaces. There is discussion of the effect of stimuli such as light, heat, pH, and electric field on changes in the morphology of the molecules at the interfaces and that of colloidal materials. The changes in the properties, such as gelation ability, dispersibility, and emulsification ability, of the resultant bulk materials containing these colloidal materials or those of the solid material are also covered. In addition, design criteria for high sensitivity, quick responsiveness, and high reversibility are presented. In each author's original system, the correlations between molecular-level responses and bulk functional responses are described as well. This book serves as an excellent guide to designing and fabricating novel, functional, eco-friendly stimuli-responsive interfaces and related materials.